2018
DOI: 10.1038/s41598-017-18757-1
|View full text |Cite
|
Sign up to set email alerts
|

Highly conserved molecular pathways, including Wnt signaling, promote functional recovery from spinal cord injury in lampreys

Abstract: In mammals, spinal cord injury (SCI) leads to dramatic losses in neurons and synaptic connections, and consequently function. Unlike mammals, lampreys are vertebrates that undergo spontaneous regeneration and achieve functional recovery after SCI. Therefore our goal was to determine the complete transcriptional responses that occur after SCI in lampreys and to identify deeply conserved pathways that promote regeneration. We performed RNA-Seq on lamprey spinal cord and brain throughout the course of functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 96 publications
5
75
0
Order By: Relevance
“…The recovery curve was well fit by an exponential process that reached a half maximum (t 1/2 ) at 2.6 ± 0.2 wpi (R 2 = 0.78, n=18 lampreys), which was similar to previous reports (Fig. 1C) (Oliphint et al, 2010; Herman et al, 2018). After spinal re-transection, this same cohort of lampreys recovered to ∼85% of normal swimming movements by 11 wpi, reaching half maximum (t 1/2 ) at 2.4 ± 0.1 wpi (R 2 = 0.78, n=18 lampreys) (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The recovery curve was well fit by an exponential process that reached a half maximum (t 1/2 ) at 2.6 ± 0.2 wpi (R 2 = 0.78, n=18 lampreys), which was similar to previous reports (Fig. 1C) (Oliphint et al, 2010; Herman et al, 2018). After spinal re-transection, this same cohort of lampreys recovered to ∼85% of normal swimming movements by 11 wpi, reaching half maximum (t 1/2 ) at 2.4 ± 0.1 wpi (R 2 = 0.78, n=18 lampreys) (Fig.…”
Section: Resultssupporting
confidence: 89%
“…After spinal transection or re-transection, the lampreys’ swimming movements were scored twice per week during the recovery periods, as previously described (Oliphint et al, 2010; Herman et al, 2018). The scoring criteria were as follows: 0 – immediately post-operatively, lampreys exhibited no response to a light tail pinch; 1 – only head movements were observed; no tail movements occurred below the lesion site; 2 – brief periods of self-initiated swimming occurred, but with atypical movements and body shapes; 3 – lampreys demonstrated longer periods of swimming with more normal undulations and fewer abnormalities; 4 – lampreys exhibited persistent bouts of swimming with normal sinusoidal undulations that were comparable to uninjured, control lampreys.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified Wnt signaling as a regulator of regeneration in multiple contexts (46)(47)(48)(49), including the retina (50-52). Thus, we examined Wnt signaling to begin to gain mechanistic insight into the molecular mechanisms underlying RPE regeneration.…”
Section: Wnt Pathway Activity Is Required For Rpe Regenerationmentioning
confidence: 99%
“…Our findings represent a prime example of how the lamprey genomes can reveal the origins of vertebrate-specific traits (66)(67)(68). The early evolutionary divergence of lampreys from the majority of living vertebrates (69-72) has repeatedly illuminated highly conserved elements of vertebrate molecular biology including basic developmental processes such as how the brain and nerves develop and revealing genes whose activity aids spinal cord healing (73).…”
Section: Discussionmentioning
confidence: 85%